Automobile active tilt control based on active suspension. (October 2018) - Yao, Jialing; Li, Zhihong; Wang, Meng; Yao, Feifan; Tang, Zheng
The rolling control of a car that focuses on reducing the roll angle passively has limited performance of increasing handling stability, passing speed, ride comfort, and rollover prevention while turning. This project presents a method for controlling an automobile to tilt toward the turning direction using active suspension. A 6-degree-of-freedom vehicle model with a 2-degree-of-freedom steering model and a 4-degree-of-freedom tilting model is established. The active tilt sliding mode controller, which causes zero steady-state tilt angle error, is established after the desired tilt angle is determined by dynamic analysis. Simulation results confirm the effectiveness of the control method. The proposed controller reduces the perceived lateral acceleration and the lateral load transfer rate, thereby effectively improving handling stability, ride comfort, and vehicle speed, meanwhile decreasing the possibility of rollover while turning.